An unusual presentation of hydatid cyst in anterior abdominal wall - Srivastava, P; Gangopadhyay, AN; Upadhyaya, VD; Sharma, SP; Jaiman, R (Kathmandu University Medical Journal, 2009)
Hydatid disease is a parasitic infestation caused by the larval form of the cestode worm Echinococcus. The most commonly encountered form of the disease is visceral hydatid cyst caused by Echinococcus granulosus or dog tapeworm. Muscular involvement has been reported in only 3-4% cases. We are reporting this case because of its rarity, difficulty to diagnose clinically, dramatic response to medical treatment and to alert the reader of this rare infestation so that open biopsy will be avoided. Key words: Hydatid cyst, parietal wall, medical treatment doi: 10.3126/kumj.v6i4.1746     Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 511-513